Intentional leadership : getting to the heart of the matter - Amaladas, Stan (Routledge, 2018)
This book provides a framework for guiding leaders to shift from linear, cause-effect thinking to an ecology of moral, intentional leadership, paying attention to how their actions are connected to others. Readers are encouraged to act in a determined, deliberate way to lead their employees, teams, and organizations to success